KAZAKH TRADITIONAL MUSIC AS A PART OF AUDIOVISUAL CULTURE OF MODERN MEDIA SPACE: ISSUES OF POPULARIZATION AND BROADCASTING (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the consideration of the cultural and communication potential of the modern media space as a medium of representation and popularization of Kazakh music. The subject of the article is traditional music as a part of cultural heritage, which is currently characterized by the predominance of audiovisual forms of digital broadcasting. The purpose of the work is to consider Kazakh traditional music as an audiovisual type in the context of modern media space.The article traces the evolution of musical communication forms from oral and written traditions to audiovisual representation, in the context of humanitarian studies of digital culture and media space. Examples of the transmission of traditional musical values through modern platforms, social networks and streaming services are given. Special attention is paid to the cultural aspect of this process, since the broadcasting of traditional music influences the musical world of society and serves to form a national identity. In the context of globalization, it is precisely national musical images presented in audiovisual forms that can serve as a means of preserving cultural memory and strengthening the values of modern society. The results of the study substantiate the audiovisual type of Kazakh traditional music in the media space, which has a high degree of impact on modern society. This allows not only to expand the listening audience, but also to ensure a deeper assimilation of musical traditions in the context of new communication realities. It also asserts the specificity of the audiovisual type and its content in the key processes of its representation and interpretation of Kazakh music. The conclusions of the study emphasize that the transmission of musical cultural values by means of modern digital media is a way to involve traditional cultural values in an audiovisual context. Purposeful work in this area should be aimed at a meaningful and artistically verified representation of the musical traditional heritage of the Kazakh people in the media space, which will serve to preserve cultural and historical memory and the formation of national identity.
Keywords: Kazakh traditional music, audiovisual type, media space, musical heritage, transmission of values, cultural policy.